A new visual indicator of chlamydial cervicitis?. Issue 1 (1st February 2000) - Sellors, J W; Walter, S D; Howard, M
Abstract : Objectives: To determine the usefulness of endocervical discharge opacity as a risk indicator for chlamydial infection in relation to two acknowledged visual indicators—yellow endocervical discharge and easily induced mucosal bleeding of the cervix. Methods: Women from two family planning clinics, a therapeutic abortion clinic, and a university student health clinic (n=1418 total) consented to a pelvic examination and chlamydia testing, and completed a questionnaire on sociodemographics, sexual behaviour, medical history, and symptoms. A case of chlamydia was defined as positive by culture or blocked enzyme immunoassay in an endocervical swab. Results: The prevalence of chlamydial infection in the clinics was 6.3%. All three of the visual indicators—yellow endocervical discharge, easily induced bleeding, and opaque cervical discharge—were statistically significantly and independently associated with chlamydial infection (odds ratios 2.8, 2.3, and 2.9 respectively), independent of clinic type. Adjustment for the other visual indicators made little difference to the odds ratios. Conclusion: Opacity of endocervical discharge was at least as important as the other two commonly acknowledged indicators of chlamydial cervicitis—yellow endocervical discharge and easily induced mucosal bleeding of the cervix.